The Path to Loyalty: Examining Shopee’s Service Attributes and Customer Satisfaction of Customers in Jakarta - Ruslim, Tommy Setiawan; Aurellia, Audrey (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: The post-pandemic period has presented challenges for e-commerce platforms, including Shopee, as they face declining customer loyalty, which affects user experience. Customer loyalty is a critical factor in sustaining business competitiveness, making it essential to understand the role of service attributes. Purpose: This study examines the impact of information quality, privacy, security, and delivery on customer loyalty among Shopee users in Jakarta. Furthermore, it investigates the role of customer satisfaction in mediating the relationship between service attributes and customer loyalty.Design/methodology/approach: The study employed a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) version 4.1.0.8 for data analysis. A total of 241 Shopee users in Jakarta were surveyed through a purposive sampling method. Data was collected using Google Forms distributed through various social media platforms, ensuring responses from active Shopee users familiar with the platform's service attributes.Finding/result: Information quality, security, and delivery positively and significantly impact customer loyalty. Information quality, privacy, security, and delivery positively and significantly influence customer satisfaction. Customer satisfaction mediates the effects of information quality, security, and delivery on customer loyalty.Conclusion: Service attributes, namely information quality, security, and delivery, are essential in influencing customer loyalty through customer satisfaction among online shopping platform users. Originality/value (State of the art): This is the first study of how service attributes influence customer loyalty among Shopee users in Jakarta through the mediating role of customer satisfaction. This study contributes to the existing literature by addressing an empirical gap and examining the influence of information quality on customer loyalty and privacy on customer satisfaction. While previous studies have explored these relationships, inconsistencies in findings highlight the need for further empirical validation. By reassessing these variables within the context of Shopee users in Jakarta, this research provides deeper insights into their roles in shaping customer satisfaction and loyalty. Keywords: Service Attributes, customer satisfaction, customer loyalty, Shopee, e-commerce